The Effect of Corporate Image and Service Quality on Loyalty with Trust Mediation - Madyaratri, Dellafanny Noor; Martaleni, Martaleni; Hendrakusuma, FX Bhakti (Journal of Economics and Management Scienties, 2025)
This research examines the influence of corporate image and service quality on customer loyalty with customer trust as a mediating variable. Conducted at Kantor Pos Trenggalek, the study highlights the importance of internal company factors in shaping customer perceptions and sustaining loyalty in service-based businesses. Using a quantitative approach, data were collected from 160 respondents through judgmental sampling and analyzed using Partial Least Square – Structural Equation Modeling (PLS-SEM). The findings indicate that both corporate image and service quality have a significant positive effect on customer trust and loyalty. Furthermore, customer trust plays a mediating role in strengthening the relationship between these variables and loyalty. This research emphasizes the strategic value of building customer trust through consistent service quality and a strong corporate image to enhance long-term loyalty. Based on the findings, it is recommended that service providers consistently maintain and improve service performance and corporate reputation to foster trust and retain loyal customers. Future studies could explore other mediating or moderating variables, such as customer satisfaction or emotional attachment, to broaden the understanding of factors influencing loyalty.